Education and Minority Groups in Afghanistan: The Case of Hazara People - Mir Hussain Amiri (Journal of Asian Social Science Research, 2023)
Afghanistan, known for its ancient history and as a centre of knowledge in the past, has seen the rise of great civilizations such as Arya, Bakhtar, and Khorasan. Education in ancient Afghanistan was influenced by the Vedic religion and later the Avestan civilization until the arrival of Islam. Education in Afghanistan is recognized as a fundamental human right that plays a crucial role in alleviating poverty, addressing inequality, and fostering sustainable development. However, the Hazara people, an ethnic and religious minority in Afghanistan, have historically been deprived of this right due to cultural, linguistic, and religious differences with the dominant Pashtun population. Hazaras have faced discrimination, marginalization, and violent persecution throughout Afghan history. They have been systematically denied access to education, employment, and political representation. Despite some progress, the Hazara people continue to face barriers to accessing quality education. Hazara students also face discrimination and harassment from peers and teachers who hold negative stereotypes of them. Moreover, Hazaras have been subjected to targeted attacks by terrorist groups like the Taliban and ISIS, resulting in loss of life and injuries. Nevertheless, Hazaras demonstrated their goodwill. They actively participated in national processes such as elections, civil society strengthening, sports, and education, showcasing their commitment to the new system. This article contributes to the study of the history of education in Afghanistan which lacks adequate analysis of education among minorities in Afghanistan like the Hazara people.